Determinants of Stock Returns with Tax Risk as a Moderating Variable - Riyan Dika Pratama; Ahmad Junaidi; Rina Yuniarti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the effects of financial performance, firm size, macroeconomic factors, and tax avoidance on stock returns, with tax risk as a moderating variable, in LQ45 companies listed on the Indonesia Stock Exchange during 2020-2024. Research methodology: This study employs a quantitative approach using secondary data obtained from annual financial reports, Bank Indonesia, and the Central Statistics Agency. The sample consists of 45 LQ45 companies selected through purposive sampling, resulting in 165 firm-year observations. Data analysis was conducted using panel data regression with Moderated Regression Analysis (MRA) through Eviews 13 to examine both direct and moderating effects. Results: The results indicate that return on assets, firm size, inflation, interest rates, and tax avoidance have no significant effect on stock returns, while the current ratio shows a negative and significant effect. Furthermore, tax risk significantly moderates the relationships between several independent variables and stock returns, either weakening or strengthening their effects depending on the level of fiscal uncertainty faced by firms. Conclusions: These findings suggest that stock returns are not solely determined by financial and macroeconomic indicators but are also influenced by fiscal uncertainty reflected in tax risk, which alters investor perceptions and market responses. Limitations: This study is limited to LQ45 companies and a five-year observation period, which may restrict the generalizability of the results to other sectors or longer time horizons. Contributions: This study provides empirical evidence of the moderating role of tax risk in stock return determination. This study contributes to the literature by integrating tax risk as a moderating variable, which remains relatively underexplored in the context of the Indonesian capital market.